TEMPO Mediated Cyclopropanols Ring Opening C−N Cross‐Coupling with Nitrogen Nucleophiles - Zhan, Jun‐Long; Zhu, Lin; Ren, Wei; Wang, Bing‐Jie; Zhao, Xin‐Ming; Zhang, Xin‐Ru; Zhang, Xin‐Yu; Xie, Yao‐Qiang (Advanced synthesis & catalysis, 2023)
A feasible and umpolung strategy for the synthesis of structurally diverse β‐amino ketones has been achieved through TEMPO mediated C−N coupling of cyclopropanols with nitrogen nucleophiles. Mechanism studies indicated that in situ generated enones derived from cyclopropanols are the key intermediates and TEMPO play multiple roles, including radical initiator, trapping reagent, a porter of β‐hydrogen and an in situ base. This protocol features broad substrate scope, good scalability and good to excellent yields and provides an alternative and complementary approach to the synthesis of structurally important β‐amino ketone scaffolds under metal and additive‐free conditions.